1990
DOI: 10.1111/j.1471-4159.1990.tb02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phospholipase C from Bacillus cereus on the Release of Membrane‐Bound Choline‐O‐Acetyltransferase from Rat Hippocampal Tissue

Abstract: Some of the enzyme choline-O-acetyltransferase (ChAT) associated with central cholinergic nerve terminals appears to be non-ionically associated with membranes. In the present study, we tested the possibility that some membrane-bound ChAT might be anchored to membranes by a phosphatidylinositol linkage by incubating rat hippocampal tissue with phospholipase C (PLC) from Bacillus cereus. The PLC selectively augmented the release of ChAT; also, the glycosylphosphatidylinositol-PLC inhibitor, zinc, blocked this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The soluble and detergent-solubilized ChAT forms appear to have similar affinities for choline and acetyl-CoA, similar molecular masses on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and similar epitope maps (Benishin and Carroll, 1983;Badamchian and Carroll, 1985;Bruce and Hersh, 1987). Insight into the possible nature of membrane-bound ChAT has been provided by Carroll and Smith (1990) and Smith and Carroll (1993), who reported that phospholipase C from Bucillus cereus and Bacillus thuringiensis, which are phosphatidylinositol-specific phospholipases, were able to release the membrane-bound form of ChAT from rat hippocampal tissue and to convert it from an amphiphilic to a hydrophilic form. This led to the proposal that at least some of the membrane-bound ChAT is anchored by an intracellular glycosylphosphatidylinositol linkage.…”
Section: Intracellular Localization Of Chatmentioning
confidence: 99%
“…The soluble and detergent-solubilized ChAT forms appear to have similar affinities for choline and acetyl-CoA, similar molecular masses on sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and similar epitope maps (Benishin and Carroll, 1983;Badamchian and Carroll, 1985;Bruce and Hersh, 1987). Insight into the possible nature of membrane-bound ChAT has been provided by Carroll and Smith (1990) and Smith and Carroll (1993), who reported that phospholipase C from Bucillus cereus and Bacillus thuringiensis, which are phosphatidylinositol-specific phospholipases, were able to release the membrane-bound form of ChAT from rat hippocampal tissue and to convert it from an amphiphilic to a hydrophilic form. This led to the proposal that at least some of the membrane-bound ChAT is anchored by an intracellular glycosylphosphatidylinositol linkage.…”
Section: Intracellular Localization Of Chatmentioning
confidence: 99%
“…The first information provided by the present work is that the sialidase contained in the pig forebrain total pellet is partly released in soluble form by treatment with a PLC specifically affecting phosphatidylinositol (B. cereus PLC) (PIPLC). In agreement with this conclusion are the observations that (a) addition of ZnClz, which inhibits PIPLC (Carrol and Smith, 1990), completely blocked sialidase liberation; (b) addition of EDTA, which inhibits the phospholipase activity on glycerophospholipids not containing inositol (Ikezawa et al, 1976), did not affect sialidase release; and (c) treatment with several proteolytic enzymes was unsuccessful in releasing sialidase. The released sialidase is distinct from the cytosolic sialidase, because this enzyme was completely washed off from the pellet (Venerando et al, 1982) before PIPLC treatment and has a pH optimum of 4.8 (Venerando et al, 1975), different from those of solubilized membrane-bound sialidase (4.2 and 6.6).…”
Section: Discussionmentioning
confidence: 62%
“…The amount of enzyme added was as follows: Pronase, 50 pg; chymotrypsin, phospholipase D, trypsin, pepsin, thermolysin, and sphingomyelinase, 100 pg; PLC (from B. thuringiensis), 0.3 unit; and PLC (from B. cereus), 1.5 units. Treatment with PLC (from B. cereus) was camed out also in the presence of ZnClz (5 mM), known to inhibit specifically the enzyme activity on phosphatidylinositol (Fox et al, 1986;Carrol and Smith, 1990), and of EDTA (1 mM), reported to inhibit selectively the enzyme activity on glycerophospholipids not containing inositol (Ikezawa et al, 1976). At the end of incubation, the mixtures were refrigerated by immersion into an ice-water bath and centrifuged at 150,000 g for 10 min.…”
Section: Sialidase Release By Treatment With Different Proteolytic Anmentioning
confidence: 99%
“…Triton X-114 was previously used to reveal the existence of hydrophilic and arnphiphilic ChAT activities in synaptosomes isolated from the electric organ of the fish Torpedo, rat brain and human nucleus caudatus (Eder-Colli er ul., 1986Docherty andBradford, 1988: Carroll andSmith, 1990) and in the differentiated rat neuroblastoma cell line NS20Y (Barochovsky et ul., 1988). ChAT activity expressed in oocytes injected with pChAT4.2 was found to partition into the detergent-depleted and detergent-enriched phases.…”
Section: Discussionmentioning
confidence: 99%